2020
DOI: 10.3389/feart.2020.00209
|View full text |Cite
|
Sign up to set email alerts
|

A Review of H2, CH4, and Hydrocarbon Formation in Experimental Serpentinization Using Network Analysis

Abstract: The origin of methane and light hydrocarbons (HCs) in natural fluids from serpentinization has commonly been attributed to the abiotic reduction of oxidized carbon by H 2 through Fischer-Tropsch-type (FTT) reactions. Multiple experimental serpentinization studies attempted to identify the parameters that control the abiotic production of H 2 , CH 4 , and light HC. H 2 is systematically and significantly formed in experiments, indicating that its production during serpentinization is well established. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 97 publications
(140 reference statements)
0
16
0
Order By: Relevance
“…Kularatne et al, 2018;Michiels et al, 2018;Brunet, 2019). We hope that this dataset and the analysis by Barbier et al (2020) stimulate complementary experiments that could fill the identified gaps; this would allow editing future versions of this dataset in a few years and potentially help people better understand the fate of carbon under highly reducing conditions such as the one produced during serpentinization.…”
Section: Discussion and Perspectivesmentioning
confidence: 98%
See 2 more Smart Citations
“…Kularatne et al, 2018;Michiels et al, 2018;Brunet, 2019). We hope that this dataset and the analysis by Barbier et al (2020) stimulate complementary experiments that could fill the identified gaps; this would allow editing future versions of this dataset in a few years and potentially help people better understand the fate of carbon under highly reducing conditions such as the one produced during serpentinization.…”
Section: Discussion and Perspectivesmentioning
confidence: 98%
“…In our recent paper (Barbier et al, 2020), we used network analysis and machine-learning algorithms to analyse a processed version of this dataset. We found that, as previously known, pressure and temperature are the two most important parameters that govern the production of H 2 and OC.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of the frequently invoked Fischer-Tropsch-type (FTT) reactions to produce methane from the abiotic reduction of oxidized carbon by H 2 is questioned. Barbier et al (2020) follow the forms and movement of carbon through the near ubiquitous, extensive serpentinization process, operating beneath most past and present seabeds.…”
mentioning
confidence: 99%
“…Nature, 436, 499-503. https://doi.org/10.1038/ nature03980. Barbier, S., Huang , F., Andreani , M., Tao , R., Hao, J., Eleish, A., Prabhu, A., Minhas, O., Fontaine, K., Fox, P., & Daniel, I.A. (2020) Conrad, R., & Seiler, W. (1979).…”
mentioning
confidence: 99%